2018
DOI: 10.1089/cap.2017.0100
|View full text |Cite
|
Sign up to set email alerts
|

Desvenlafaxine Versus Placebo in a Fluoxetine-Referenced Study of Children and Adolescents with Major Depressive Disorder

Abstract: Objectives: To evaluate the short-term efficacy and safety of desvenlafaxine (25–50 mg/d) compared with placebo in children and adolescents with major depressive disorder (MDD).Methods: Outpatient children (7–11 years) and adolescents (12–17 years) who met DSM-IV-TR criteria for MDD and had screening and baseline Children's Depression Rating Scale–Revised (CDRS-R) total scores >40 were randomly assigned to 8-week treatment with placebo, desvenlafaxine (25, 35, or 50 mg/d based on baseline weight), or fluoxetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 48 publications
1
15
1
Order By: Relevance
“…We also examined two recent desvenlafaxine trials for youth depression, neither of which demonstrated efficacy for desvenlafaxine (52,53). Across the two trials, we did not observe clear trends in suicidality as reported via adverse events or on the C-SSRS.…”
Section: Recent Clinical Trialsmentioning
confidence: 85%
“…We also examined two recent desvenlafaxine trials for youth depression, neither of which demonstrated efficacy for desvenlafaxine (52,53). Across the two trials, we did not observe clear trends in suicidality as reported via adverse events or on the C-SSRS.…”
Section: Recent Clinical Trialsmentioning
confidence: 85%
“…Principal investigators were child and adolescent or general psychiatrists with experience in the diagnosis and treatment of pediatric depression and in conducting industry-sponsored studies; evaluator qualifications and training were previously described. 27,28 Lead-in studies were similarly designed phase 3, multicenter, randomized, double-blind, placebo-controlled trials. Participants enrolled in the lead-in for study 1030 were randomly assigned (1:1:1) to placebo, desvenlafaxine low exposure (20-35 mg/d), or desvenlafaxine higher exposure (25-50 mg/d), with desvenlafaxine dose based on body weight at baseline (Supplemental Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Enrollment criteria for the lead-in studies are described in detail in separate publications. 27,28 Briefly, those enrolled included male and female outpatients, aged 7 years to less than 18 years who at time of enrollment met Diagnostic and Statistical Manual of Mental Disorders (4th ed., Text Revision) criteria for MDD as the primary diagnosis, as assessed by the KIDDIE Schedule for Affective Disorders and Schizophrenia for School-Age Children-Present and Lifetime Version 30 (K-SADS-PL) and clinical interview. A comprehensive diagnostic psychiatric evaluation, including collection of psychiatric history and treatments and confirmation of the MDD diagnosis, was performed by a psychiatrist at screening of the lead-in study.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations